A Bourdieusian Analysis of the Cultural Arbitraries in the Educational System for Chinese People in the Post WWII Hong Kong, 1940s–1970s. Issue 2 (3rd April 2021) - Li, Yulong; Liu, Xiaojing
ABSTRACT: When Hong Kong became a British colony in 1842, the educational system was not centralized. However, after World War II, a wave of decolonization swarmed the globe. In 1945 an internal war broke out between the Chinese Communists and the Nationalists, resulting in the founding of the People's Republic of China in 1949, and the Nationalists' retreat to the Taiwan region. Both sides attempted to shape the direction of education to influence Chinese habitants in Hong Kong. The British colonizer in Hong Kong, in order to safeguard their vested interests, decided to centralize the Chinese people's education and impose a series of curricular reforms, which acted to instill negative feelings or political indifference towards China among younger Hong Kong residents. Following the Bourdieusian theory of social reproduction by educational means, this paper proposes to foster and develop critical thinking regarding the colonial history of Hong Kong and the changing nature of the local Chinese identity as fostered in the school curriculum. This study found that the British colonizer imposed cultural arbitraries in the pedagogic action of the colonial Chinese curriculum and gradually established a colonial educational system that guaranteed the reproduction of the Hong Kong residents with little Chinese nationalism.